Depression symptoms in neurological patients: A survey of a large cohort of patients with focal brain lesions. Issue 7 (9th August 2022) - Brandt, Emma M.; Trapp, Nicholas T.; Boes, Aaron D.; Tranel, Daniel
ABSTRACT: Introduction: Examining depression following neurological injury is useful for understanding post-lesion depression and depression more generally. The extant literature shows variability in the incidence and severity of depression post-lesion, likely due to heterogeneity in study methodology, patient samples, measures of depression, and time of assessment. Here, we aim to characterize depression symptoms and their demographic correlates in a large sample of individuals in the chronic epoch following a focal brain lesion. Method: We sampled 492 individuals who had focal, stable brain lesions and were in the chronic epoch (≥3 months post-onset). Demographic (gender, years of education), temporal (age at lesion onset, time since lesion onset), and lesion (lesion laterality, lesion etiology, lesion volume) factors were used to predict depression symptoms measured by the Beck Depression Inventory (BDI). Results: We found that on average, neurological patients exhibited elevated levels of depression symptoms (although not clinically significant) relative to a community sample, and the neurological patients showed higher rates of mild and moderate depression symptoms than are typical in a community sample. Gender and lesion etiology were predictive of depression symptoms, whereby women and patients with ischemic stroke had higher levels of depression symptoms. Conclusions: Our results suggest that depression symptom severity may be elevated following a focal brain lesion. Moreover, some individuals may be more likely to develop depression symptoms post-lesion than others. This may be mediated by individual factors such as gender and lesion etiology. The findings have important implications for the diagnosis, prognosis, and treatment of depression in neurological patients.